The nature and identity of apologetics in light of the calls of scripture and the Second Vatican Council - Nicolson, Stuart (Jihočeská univerzita, 2023)
Apologetics in recent times has had for many a negative value, and the term 'apologetics' did not appear in the Second Vatican Council documents. However, by returning to the sources in Scripture and the Early Church, especially Peter's call (1Peter 3:15-16) for all faithful to be ready to respond when questioned or challenged about their faith, and to do so in a Christian manner, apologetics can be understood as far more original, ordinary, and organic than how it is often defined. It was originally an integral part of Christians speaking out about their faith, participating with the Logos. Through a Petrine lens, apologetical calls and content can be identified in 10 of the 16 Vatican II documents, including two clear paraphrases of Peter's call. This indicates a problem in how apologetics is identified and understood. Part 1 provides a working definition for Petrine apologetics in order to identify its development through Christian history. Part 2 present a brief and selective history of apologetics. Petrine apologetics is observed and explored in Scripture in Part 2a, including in Jesus' ministry and the first Church generations. In Part 2b it is shown how a second century apologetical turn, particularly through Justin Martyr, reinforced by Eusebius, and concretised by several later Early Church Fathers, narrowed apologetics into becoming elite, intellectual, and clerical - not for all the faithful but the few. The Mediaeval period (Part 2c) could have seen a return to more universal Petrine apologetics, especially through the Fourth Lateran Council, but weak dissemination of its teachings meant the opportunity was lost. After the Reformation, in Part 2d, Charles Borromeo's pastoral apologetics stands out, as well as a growing movement based upon credibility in the English-speaking sphere where apologetics was becoming part of organic engagement of Catholics in Protestant societies. Part 3 focuses on Vatican II. The entrenched Justinian approach in Catholic Europe eschewed engagement with others, leaving apologetics as overly catechetical. Balthasar identified and rejected the old paradigm and the main reform ideas, calling for a new approach: Love Alone Is Credible. Many conciliar apologetics themes are congruent with his reform call, and with Petrine apologetics. In addition to apologetical calls, Vatican II shows that apologetical preparation should be embedded in Christian education (Gravissimum Educationis 2) and how apologetically prepared faithful should engage with society (Apostolicam Actuositatem 1, 2, 11, 29, 31, etc.). But the Council's apologetics calls were not developed and apologetics was mostly replaced by fundamental theology, which has problematic features from Justinian apologetics and the reform ideas Balthasar rejected, and is not related to the apologetical calls of Peter or Vatican II. However, there has been an organic development of apologetics since the 1980s. In Part 4, the problematic current state of Catholic understanding in the ordinary faithful is evident in two recent surveys. It is necessary to respond to this. By reframing apologetics according to the original Petrine call and its Vatican II confirmation, a New Apologetics (NA) can be developed that emphasises Peter's elements of preparation, response, in a Christian manner, for all the faithful. The Petrine elements are unpacked in today's context and several distinctions are explored, including objective and subjective approaches, and the spectrum of evangelisation-apologetics-catechetics. Three 'voices' are shown to have particularly contributed so far to NA: William Levada, Robert Barron, and Peter Kreeft. All intellectual and two being clerics, they have the insight and ability to guide developments. Looking forwards, the two named conciliar texts are explored in how they can be unpacked for developing an embedded apologetics of preparation, response, in a Christian manner: original, organic, ordinary apologetics.
The nature and identity of apologetics in light of the calls of scripture and the Second Vatican Council
Keywords: Apologetics; Apostolicam Actuositatem; Balthasar; Christian manner; Avery Dulles; Education; Engagement; Gravissimum Educationis; Justinian apologetics; Laity; New Apologetics; Ordinary apologetics; Organic apologetics; Original apologetics; Participation; Pastoral apologetics; Peter's call; Petrine apologetics; Practical apologetics; Preparation; Reframing; Response; Ressourcement; Second Vatican Council; Apologetics; Apostolicam Actuositatem; Balthasar; Christian manner; Avery Dulles; Education; Engagement; Gravissimum Educationis; Justinian apologetics; Laity; New Apologetics; Ordinary apologetics; Organic apologetics; Original apologetics; Participation; Pastoral apologetics; Peter's call; Petrine apologetics; Practical apologetics; Preparation; Reframing; Response; Ressourcement; Second Vatican Council